Plasmon resonances and tunneling in sub-nanometric systems (2016)
In this thesis we have theoretically studied the optical response of several canonical Systems with narrow gaps: nanoparticle pairs (dimers), and core-shell systems (known in literature as nanomatryoshkas), in the subnanometric regime (systems below 10 nm). As a first approach, we have used classical electromagnetics treatment allowing a link with previous studies and characterisation of the plasmonic modes and near and far fields. We have explored the physics of the plasmon coupling and near field enhancements in plasmonic cavities upon reduction of the gap size, where classical theory predicts extremely strong effects because of the attractive Coulomb interaction between plasmon induced charges across the junction. For the vanishing width of the junction this interaction diverges leading to the discontinuities in classical theory. This is precisely the regime where quantum effects like tunneling are of paramount importance as they neutralise the screening charges and allow continuous transition from the capacitive to inductive coupling at zero gap size (continuos metal in the junction)